Heterogeneous Integration of Vertical GaN Power Transistor on Si Capacitor for DC-DC Converters - Yu, Zechun; Zeltner, Stefan; Boettcher, Norman; Rattmann, Gudrun; Leib, Juergen; Bayer, Christoph; Schletz, Andreas; Erlbacher, Tobias; Frey, Lothar (7th Electronic System-Integration Technology Conference, ESTC 2018, 2018)
Keywords: Vertical GaN; 3D Integration; Si-Capacitor; Ag-Ag direct bonding

Integration of printed electronics with potted power electronic modules - Zimmermann, Victoria; Zörner, Alicia; Chen, Weiyi; Yu, Zechun; Jank, Michael; Bayer, Christoph; Schletz, Andreas; März, Martin (CIPS 2020 - 11th International Conference on Integrated Power Electronics Systems, 2020)
Printed electronics on flexible substrates are attractive for various applications in the field of sensor technology. This work aims at investigating the integration of printed electronics in potted power-electronic modules. Silver (Ag) interdigitated structures with varying electrode dimensions were printed on polyimide and polyethylene terephthalate foil and afterwards potted with Wacker SilGel® 612. Printing ability, adhesion to potting material, and contacting were investigated. Capacitance-voltage measurements were performed to characterize the behavior of printed devices in contact with potting material. Peel tests were performed in order to gain information on the adhesion of different substrate materials to the SilGel. Further, different contacting methods were evaluated. Based on the presented results, the integration of printed electronics in potted power electronic modules is highly feasible and could allow the facile addition of monitoring devices.
CRIS-Team Scopus Importer:2021-04-19